Herstellung und Charakterisierung mechanisch flexibler organischer Solarzellen durch Flüssigprozessierung - Nickel, Felix (KIT Scientific Publishing, 2014)
This document presents the development and optoelectronic analysis of a flexible electrode system. The focus is the application of all functional layers out of solution to enable a cost effective processing with large area print and coating techniques. Moreover, the mechanical stability of the electrode system and the complete solar cell is investigated by tensile tests.